Answer:
y = 3/7x - 6
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
- Equality Properties
<u>Algebra I</u>
Slope-Intercept Form: y = mx + b
Step-by-step explanation:
<u>Step 1: Define</u>
Slope <em>m</em> = 3/7
Point (14, 0)
<u>Step 2: Find y-intercept </u><em><u>b</u></em>
- Substitute: 0 = 3/7(14) + b
- Multiply: 0 = 6 + b
- Isolate <em>b</em>: -6 = b
- Rewrite: b = -6
<u>Step 3: Write linear equation</u>
y = 3/7x - 6
12 if not just look it up on quiz lit and you’ll get it it’s on safari or use scan and solve
Answer:
![3 (a + 5b) + a (a + 4) = a^2 + 7a + 15b](https://tex.z-dn.net/?f=3%20%28a%20%2B%205b%29%20%2B%20a%20%28a%20%2B%204%29%20%20%3D%20a%5E2%20%2B%207a%20%2B%2015b)
![y (10 - y) + 3 (y - 2) = - y^2+13y - 6](https://tex.z-dn.net/?f=y%20%2810%20-%20y%29%20%2B%203%20%28y%20-%202%29%20%20%3D%20-%20y%5E2%2B13y%20-%206)
![2 (8a - 5b) + 3 (5a - 12) = 31a -10b - 36](https://tex.z-dn.net/?f=2%20%288a%20-%205b%29%20%2B%203%20%285a%20-%2012%29%20%20%3D%2031a%20-10b%20%20-%2036)
![3 (y - 3) + ( 8 - 6y + x) = -3y + x-1](https://tex.z-dn.net/?f=3%20%28y%20-%203%29%20%2B%20%28%208%20-%206y%20%2B%20x%29%20%3D%20-3y%20%2B%20x-1)
![a (a - 2b) + b (b + 2a - c) =a^2 + b^2 - bc](https://tex.z-dn.net/?f=a%20%28a%20-%202b%29%20%2B%20b%20%28b%20%2B%202a%20-%20c%29%20%3Da%5E2%20%20%2B%20b%5E2%20%20-%20bc)
![5 (x - y + z) + (4x + 3y) =9x - 2y +5z](https://tex.z-dn.net/?f=5%20%28x%20-%20y%20%2B%20z%29%20%2B%20%284x%20%2B%203y%29%20%3D9x%20-%202y%20%2B5z)
Step-by-step explanation:
Solving (i):
![3 (a + 5b) + a (a + 4)](https://tex.z-dn.net/?f=3%20%28a%20%2B%205b%29%20%2B%20a%20%28a%20%2B%204%29)
Open brackets
![3 (a + 5b) + a (a + 4) = 3a + 15b + a^2 + 4a](https://tex.z-dn.net/?f=3%20%28a%20%2B%205b%29%20%2B%20a%20%28a%20%2B%204%29%20%20%3D%203a%20%2B%2015b%20%2B%20a%5E2%20%2B%204a)
Collect like terms
![3 (a + 5b) + a (a + 4) = a^2 + 4a+3a + 15b](https://tex.z-dn.net/?f=3%20%28a%20%2B%205b%29%20%2B%20a%20%28a%20%2B%204%29%20%20%3D%20a%5E2%20%2B%204a%2B3a%20%2B%2015b)
![3 (a + 5b) + a (a + 4) = a^2 + 7a + 15b](https://tex.z-dn.net/?f=3%20%28a%20%2B%205b%29%20%2B%20a%20%28a%20%2B%204%29%20%20%3D%20a%5E2%20%2B%207a%20%2B%2015b)
Solving (ii)
![y (10 - y) + 3 (y - 2)](https://tex.z-dn.net/?f=y%20%2810%20-%20y%29%20%2B%203%20%28y%20-%202%29)
Open bracket
![y (10 - y) + 3 (y - 2) = 10y - y^2 + 3y - 6](https://tex.z-dn.net/?f=y%20%2810%20-%20y%29%20%2B%203%20%28y%20-%202%29%20%20%3D%2010y%20-%20y%5E2%20%2B%203y%20-%206)
Collect like terms
![y (10 - y) + 3 (y - 2) = - y^2+10y + 3y - 6](https://tex.z-dn.net/?f=y%20%2810%20-%20y%29%20%2B%203%20%28y%20-%202%29%20%20%3D%20-%20y%5E2%2B10y%20%20%2B%203y%20-%206)
![y (10 - y) + 3 (y - 2) = - y^2+13y - 6](https://tex.z-dn.net/?f=y%20%2810%20-%20y%29%20%2B%203%20%28y%20-%202%29%20%20%3D%20-%20y%5E2%2B13y%20-%206)
Solving (iii)
![2 (8a - 5b) + 3 (5a - 12)](https://tex.z-dn.net/?f=2%20%288a%20-%205b%29%20%2B%203%20%285a%20-%2012%29)
Open bracket
![2 (8a - 5b) + 3 (5a - 12) = 16a -10b + 15a - 36](https://tex.z-dn.net/?f=2%20%288a%20-%205b%29%20%2B%203%20%285a%20-%2012%29%20%20%3D%2016a%20-10b%20%2B%2015a%20-%2036)
Collect like terms
![2 (8a - 5b) + 3 (5a - 12) = 16a+ 15a -10b - 36](https://tex.z-dn.net/?f=2%20%288a%20-%205b%29%20%2B%203%20%285a%20-%2012%29%20%20%3D%2016a%2B%2015a%20-10b%20%20-%2036)
![2 (8a - 5b) + 3 (5a - 12) = 31a -10b - 36](https://tex.z-dn.net/?f=2%20%288a%20-%205b%29%20%2B%203%20%285a%20-%2012%29%20%20%3D%2031a%20-10b%20%20-%2036)
Solving (iv)
![3 (y - 3) + ( 8 - 6y + x)](https://tex.z-dn.net/?f=3%20%28y%20-%203%29%20%2B%20%28%208%20-%206y%20%2B%20x%29)
Open bracket
![3 (y - 3) + ( 8 - 6y + x) = 3y - 9 + 8 - 6y + x](https://tex.z-dn.net/?f=3%20%28y%20-%203%29%20%2B%20%28%208%20-%206y%20%2B%20x%29%20%3D%203y%20-%209%20%2B%208%20-%206y%20%2B%20x)
Collect like terms
![3 (y - 3) + ( 8 - 6y + x) = 3y - 6y + x- 9 + 8](https://tex.z-dn.net/?f=3%20%28y%20-%203%29%20%2B%20%28%208%20-%206y%20%2B%20x%29%20%3D%203y%20%20-%206y%20%2B%20x-%209%20%2B%208)
![3 (y - 3) + ( 8 - 6y + x) = -3y + x-1](https://tex.z-dn.net/?f=3%20%28y%20-%203%29%20%2B%20%28%208%20-%206y%20%2B%20x%29%20%3D%20-3y%20%2B%20x-1)
Solving (v):
![a (a - 2b) + b (b + 2a - c)](https://tex.z-dn.net/?f=a%20%28a%20-%202b%29%20%2B%20b%20%28b%20%2B%202a%20-%20c%29)
Open bracket
![a (a - 2b) + b (b + 2a - c) =a^2 - 2ab + b^2 + 2ab - bc](https://tex.z-dn.net/?f=a%20%28a%20-%202b%29%20%2B%20b%20%28b%20%2B%202a%20-%20c%29%20%3Da%5E2%20-%202ab%20%2B%20b%5E2%20%2B%202ab%20-%20bc)
Collect like terms
![a (a - 2b) + b (b + 2a - c) =a^2 + 2ab- 2ab + b^2 - bc](https://tex.z-dn.net/?f=a%20%28a%20-%202b%29%20%2B%20b%20%28b%20%2B%202a%20-%20c%29%20%3Da%5E2%20%2B%202ab-%202ab%20%2B%20b%5E2%20%20-%20bc)
![a (a - 2b) + b (b + 2a - c) =a^2 + b^2 - bc](https://tex.z-dn.net/?f=a%20%28a%20-%202b%29%20%2B%20b%20%28b%20%2B%202a%20-%20c%29%20%3Da%5E2%20%20%2B%20b%5E2%20%20-%20bc)
Solving (vi)
![5 (x - y + z) + (4x + 3y)](https://tex.z-dn.net/?f=5%20%28x%20-%20y%20%2B%20z%29%20%2B%20%284x%20%2B%203y%29)
Open brackets
![5 (x - y + z) + (4x + 3y) =5x - 5y +5z+4x +3y](https://tex.z-dn.net/?f=5%20%28x%20-%20y%20%2B%20z%29%20%2B%20%284x%20%2B%203y%29%20%3D5x%20-%205y%20%2B5z%2B4x%20%2B3y)
Collect like terms
![5 (x - y + z) + (4x + 3y) =5x +4x +3y- 5y +5z](https://tex.z-dn.net/?f=5%20%28x%20-%20y%20%2B%20z%29%20%2B%20%284x%20%2B%203y%29%20%3D5x%20%2B4x%20%2B3y-%205y%20%2B5z)
Answer:
1/3
Step-by-step explanation:
Slope is always represented by m in the equation y=mx+b. Therefore, the value that is attached to the x is always the slope.
1271 if 30 and 40 were the originals and raised by one